A new PPP one-way timing approach via BDS-3 PPP-B2b and short-message communication service - Wang, Yong; Ge, Yulong; Jiang, Weiping; Liu, Tianjun (Measurement : journal of the International Measurement Confederation, 2025)
•Proposed a new PPP one-way timing method based on PPP-B2b and GSMC service.•Clock prediction model is promoted to account for the transmission delay.•Studied the performance of the new PPP one-way timing method. In the realm of time-frequency, precise point positioning (PPP) technology has been widely used, the current PPP time transfer or timing necessitates network communication for data transmission, which consequently leads to a reduction in the reliability of PPP timing. Based on the BDS-3 PPP service (PPP-B2b) and the global short message communication (GSMC) service, this study proposes a novel PPP one-way timing method that is not subject to distance limitations or the requirements of network communication. Users can directly obtain the difference with UTC(k). Then, the proposed PPP timing method was validated using four stations equipped with external high-performance atomic clocks, based on a dataset of eight days. According to the findings, the suggested PPP one-way timing technique might reach a timing accuracy of roughly 0.5 ns in environments without a network. In terms of frequency stability, the proposed PPP timing method exhibits a stability of approximately 1.4 × 10−13 at 960 s and a stability of about 3 × 10−14 at 15360 s. Further, even under GSMC communication delays of 1 min, 5 min, and 10 min, the proposed PPP one-way timing accuracy can still achieve better than 0.5 ns.